2014
DOI: 10.1051/0004-6361/201424458
|View full text |Cite
|
Sign up to set email alerts
|

V838 Monocerotis: the central star and its environment a decade after outburst

Abstract: Aims. V838 Monocerotis erupted in 2002, brightened in a series of outbursts, and eventually developed a spectacular light echo. A very red star emerged a few months after the outburst. The whole event has been interpreted as the result of a merger. Results. A significant new result is the detection of a compact structure around V838 Mon, as seen from MIDI data. The extension of the structure increases from a FWHM of 25 mas at 8 µm to 70 mas at 13 µm. At the adopted distance of D = 6.1 ± 0.6 kpc, the dust is di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 36 publications
5
35
0
Order By: Relevance
“…3). It is also consistent with VLTI observations of the region at MIR wavelengths (Chesneau et al 2014). The dust density was assumed to increase with distance from V838 Mon as r 0.75 .…”
Section: Dustsupporting
confidence: 91%
“…3). It is also consistent with VLTI observations of the region at MIR wavelengths (Chesneau et al 2014). The dust density was assumed to increase with distance from V838 Mon as r 0.75 .…”
Section: Dustsupporting
confidence: 91%
“…In fact this is probably not really the case. As well as the finding of Chesneau et al (2014), evidence for a non-spherical morphology comes from Wisniewksi et al (2003b). They found that spectroscopic and spectropolarimetric variations took place during the outburst, this being indicative of asymmetric geometry; this result is backed up the study of Desidera et al (2004), who also found polarimetric changes during 2002.…”
Section: Point Sourcementioning
confidence: 75%
“…Interferometry carried out with the Very Large Telescope Interferometer (VLTI) was the one to resolve disks around post-AGB stars (Deroo et al, 2006, Section 4.2.2), not to mention a host of disks and tori nested inside the cores of pre-planetary nebulae (PNe) (e.g., Chesneau et al, 2007) or in newly exploded stars thought to be the product of a merger (e.g., Chesneau et al, 2014, Section 7). Today, thanks to Spectro-Polarimetric High-contrast Exoplanet REsearch , SPHERE, detailed observations are being taken of AGB systems such as LB Pup where a (presumed) binary causes a bipolar outflow (Kervella et al, 2015).…”
Section: The Binary Star Toolkitmentioning
confidence: 99%